2019
DOI: 10.1017/s0025315419001048
|View full text |Cite
|
Sign up to set email alerts
|

Strongholds of Ostrea edulis populations in estuaries in Essex, SE England and their association with traditional oyster aquaculture: evidence to support a MPA designation

Abstract: The flat oyster Ostrea edulis has declined significantly in European waters since the 1850s as a result of anthropogenic activity. Ostrea edulis was designated a UK Biodiversity Action Plan Species and Habitat in 1995, and as a Feature of Conservation Importance (FOCI) within the UK Marine & Coastal Access Act 2009. To promote the recovery of oyster beds, a greater understanding of its abundance and distribution is required. Distribution of O. edulis across the proposed Blackwater, Crouch, Roach and Colne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In the case of O. edulis in Europe, reference sites that may provide a baseline for assessing the progress of restoration efforts are absent from much of the range. Moreover, sites that still contain populations are generally modified as a result of a history of oyster production, dredging and other fishing activities, or modified via shifts in the dominant biotic community (Allison, Hardy, Hayward, Cameron, & Underwood, 2019; Helmer et al, 2019; Preston et al, 2020). As such, establishing reasonable baselines to inform adaptive management of restoration efforts where O. edulis habitats are currently absent is a key priority.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of O. edulis in Europe, reference sites that may provide a baseline for assessing the progress of restoration efforts are absent from much of the range. Moreover, sites that still contain populations are generally modified as a result of a history of oyster production, dredging and other fishing activities, or modified via shifts in the dominant biotic community (Allison, Hardy, Hayward, Cameron, & Underwood, 2019; Helmer et al, 2019; Preston et al, 2020). As such, establishing reasonable baselines to inform adaptive management of restoration efforts where O. edulis habitats are currently absent is a key priority.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent study in Essex, UK found little explanatory power of abiotic variables such as temperature and pH in explaining the occurrence of O. edulis . Occurrence and abundance were instead predominantly determined by the presence of shell (Allison et al, 2019). Given that O. edulis is largely extirpated from much of its range, there is a significant role to be played by habitat suitability models in identifying suitable locations if appropriate input data can be improved (see Gormley, Porter, Bell, Hull, & Sanderson, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…While not yet common in oyster restoration in Europe there is also a long history of restoration and conservation interventions for restoring traditional shellfish fisheries (Allison, Hardy, Hayward, Cameron, & Underwood, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These range from potential biodiversity benefits from the presence of flat oyster beds or reefs (Lown, 2019; Pogoda, 2019) to potential filtration benefits resulting in increased water quality (Rodriguez‐Perez et al, 2019; Wilson, 1983). While not yet common in oyster restoration in Europe there is also a long history of restoration and conservation interventions for restoring traditional shellfish fisheries (Allison, Hardy, Hayward, Cameron, & Underwood, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation